An ultrawideband monopulse feed with slant polarization for tracking radar systems - Davood Zarifi; Ali Farahbakhsh; Michal Mrozowski (Scientific Reports)
Abstract An ultrawideband slant-polarized monopulse feed is designed and fabricated for microwave applications. The proposed configuration features four end-launched diagonal horns allowing for the production of sum and difference channels in two principal planes. The key advantage of this proposed monopulse antenna over traditional monopulse feeds is its ability to combine the benefits of ultrawideband performance with slant polarization while maintaining acceptable side lobe level. The design is validated by fabricating a prototype of the proposed feed antenna. Measurement results are in a reasonable agreement with the simulations. The measured ratio bandwidth is 2.5:1 from 8 to 18 GHz with a peak gain of 17.92 dBi. The null depth in the difference patterns is approximately − 32 dB. Given these characteristics, the proposed monopulse feed is a suitable choice for use in commercial tracking radar systems that require wide bandwidth and slant polarization, such as those found in satellite-based applications.